Introduction to the development technology of earthquake quick report information software - Chongxiao Xi; Xiang Gao; Xuexia Xin; Chunlian Li (地震科学进展, 2022)
Accurate and rapid release of earthquake quick report information is a standard to measure the information service level and ability of earthquake industry, and also reflects the social service ability of earthquake system. In this paper, the development technology of earthquake quick report information software products and earthquake auxiliary products based on JOPENS system and EQIM system developed by Provincial Earthquake Agency are introduced, for the developers to achieve rapid release of earthquake reports and related information, select the system data for their own needs to provide a reference for the second development.